Hakikat serta Pengembangan Ilmu Pengetahuan dan Teknologi dalam Pandangan Islam - Lasmanah Lasmanah; Fitria Khoirunnisa; Ika Ika (LPPM Politeknik Pratama, 2023)
Connecting the development of science with religion makes human beings have an important role in widespread knowledge, both secular and ukhrawi. As a grip in living life interrelated with each other to complement and solve the problems that occurred in this and future generations so that science and religion can give influence both from various groups of Islamic people and other religions. Research methods that use descriptive analytics aim to clearly describe the object that is naturally studied. King Abdullah University of Science and Technology (KAUST) became the first educational institution in Saudi Arabia to allow male and female students to sit in one room, guarantee creative freedom, and implement the highest international standards in terms of research and education supported by state-of-the-art laboratories. The development of this project in the field of science and technology directs its research programs to support the future of Saudi Arabia in the post-oil era, in areas of research that exploit solar energy and modern agriculture in extremely rough, dry, and hot climates. With the advancement of science and technology, man can glorify the earth of God.